Penerapan Keran Wudu Otomatis pada Optimasi Penggunaan Air dengan Sensor Ultrasonic Berbasis Arduino dengan Sistem Back Up Daya Otomatis - Nurhikmah Fajar; Nur Azhary Iriawan Eka Putra; Isminarti Isminarti; Mohamad Ilyas Abas (Journal of Computer System and Informatics (JoSYC), 2023)
A resource is a potential value possessed by a particular material or element in life. Water is a resource that is a basic human need for survival, both for living needs and spiritual needs, even up to the era of modern technology. The level of human well-being is measured by the fulfillment of social, economic, and spiritual needs, including the need for automated technology to make work easier and more efficient. The need for automatic equipment in every field is increasing due to considerations of its practical and efficient nature, including spiritual needs. Spiritual activities that can apply automatic technology include the ablution process. The ablution is a mandatory routine activity. Water users in the process of taking wudu water are not optimal because when they want to perform wudu the tap lever is immediately turned, while they still need time to prepare themselves, for example by removing the hijab or rolling up the sleeves of their clothes. The water will flow continuously until the ablution process is complete and the tap lever is turned to close the water flow. So, in this case, a lot of water is wasted. Applying automatic technology to the wudu faucet requires a continuous supply of electricity so that it always remains operational by providing a backup power supply that charges automatically so that the wudu process can be carried out at any time. The use of Arduino and the PING HC-SR04 ultrasonic sensor as an object distance detector can make the tap automatic and therefore practical. The working principle of this automatic faucet is that the solenoid will activate when the sensor detects an object under the faucet at a distance of 5 to 40 cm. The maximum detection angle is 10°. The average efficiency of automatic faucets compared to manual faucets is ±30.09%.